Divide and conquer. (Economist, 1996)
The writer considers whether a network of personal computers (PCs), or a parallel computer, might prove to be as formidable a number cruncher as a supercomputer. Several of the difficulties involved in making a parallel computer out of linked PCs instead of the nodes that are all linked inside a supercomputer are discussed. Details of work carried out by Piete Brooks of the University of Cambridge and Andrew Grimshaw of the University of Virginia in Charlottesville to overcome these difficulties are outlined.